Cystic Fibrosis Diagnosed Using Indigenously Wrapped Sweating Technique: First Large-Scale Study Reporting Socio-Demographic, Clinical, and Laboratory Features among the Children in Bangladesh A Lower Middle Income Country - ARM Luthful Kabir MBBS, FCPS; Sudipta Roy MBBS, FCPS; Rahat Bin Habib MBBS, MD; Kazi Selim Anwar MD, MPhil; Md. Abid Hossain Mollah MBBS, FCPS, Dip. in Med Edu, FRCP; Ruhul Amin MBBS, FCPS; Al Amin Mridha MBBS, MD, FCPS, FRCP; Jasim Uddin Majumder MBBS, MD, FCPS; Md. Delwar Hossain MBBS, FCPS; Nazmul Haque MPhil; Shakil Ahmed MBBS, MD, FCPS; Mohammod Jobayer Chisti MBBS, MMed, PhD (SAGE Publishing, 2020)
Due to lack of robust data on childhood cystic fibrosis (CF) in Bangladesh we sought to evaluate their clinico-epidemiology. A cross-sectional observation was conducted adopting CF-foundation consensus-panel-diagnostic criteria in 3 tertiary-care-hospitals in Bangladesh from 2000 to 2017. Clinically suspected 95 CF-cases were subjected to sweat-chloride testing using locally-developed a fast, cheap and effective indigenously body-wrapped sweating technique measured by US-Easy Lyte-automated microprocessor-controlled analyzer marking ≥60 mmol/L as positive. Mean-age of CF-cases at disease-onset was 16.9 ± 26.6 months that significantly differed with age-at-diagnosis ( P  < .02). Pulmonary syndromes included chronic wet cough in 100%, respiratory distress in 90.5%, digital-clubbing in 78%, mucopurulent-sputum in 74%-cases, and crepitation in 82%. Radio-imaging revealed bronchiectasis in 60%, hyperinflation/peribronchial-thickening in 22% and, pan-sinusitis in 89%-cases. While 37% had history-of malabsorption, high-fecal-fat revealed in 53%-cases. Malnutrition prevailed as severe-underweight in 87%-cases and all CF-cases (100%) had high sweat-chloride (mean = 118 ± 53.34 mmol/L). Thus, children with pulmonary features coupled with severe malnutrition and associated radio-imaging bronchiectasis should be screened for CF with a fast, cheap and effective sweat test in resource poor settings.